Rapamycin and abundant TCR stimulation are required for the generation of stable human induced regulatory T cells. Issue 12 (14th December 2020) - Kim, Juewan; Hope, Christopher M; Perkins, Griffith B; Stead, Sebastian O; Scaffidi, Jacqueline C; Kette, Francis D; Carroll, Robert P; Barry, Simon C; Coates, Patrick Toby
Abstract: Objectives: Regulatory T cells (Tregs) are a vital sub‐population of CD4 + T cells with major roles in immune tolerance and homeostasis. Given such properties, the use of regulatory T cells for immunotherapies has been extensively investigated, with a focus on adoptive transfer of ex vivo expanded natural Tregs (nTregs). For immunotherapies, induced Tregs (iTregs), generated in vitro from naïve CD4 + T cells, provide an attractive alternative, given the ease of generating cell numbers required for clinical dosage. While the combination of TGF‐β, ATRA and rapamycin has been shown to generate highly suppressive iTregs, the challenge for therapeutic iTreg generation has been their instability. Here, we investigate the impact of rapamycin concentrations and α‐CD3/CD28 bead ratios on human iTreg stability. Methods: We assess iTregs generated with various concentrations of rapamycin and differing ratios of α‐CD3/CD28 beads for their differentiation, stability, expression of Treg signature molecules and T helper effector cytokines, and Treg‐specific demethylation region (TSDR) status. Results: iTregs generated in the presence of TGF‐β, ATRA, rapamycin and a higher ratio of α‐CD3/CD28 beads were highly suppressive and stable upon in vitro re‐stimulation. These iTregs exhibited a similar expression profile of Treg signature molecules and T helper effector cytokines to nTregs, in the absence of TSDR demethylation. Conclusion: This work establishes a method to generate human iTregs which maintain stable phenotype and function upon in vitro re‐stimulation. Further validation in pre‐clinical models will be needed to ensure its suitability for applications in adoptive transfer. Abstract : Induced regulatory T cells are an attractive alternative for adoptive transfer in an allogeneic transplant setting. We report that rapamycin and abundant TCR stimulation are required to generate stable human induced regulatory T cells.